Is Narayan’s Bharati a Crocus of an Ideal Indian Woman? - Reshma Tabassum (European Scientific Journal, ESJ, 2022)
India is a land with deep-rooted value system. Exhibiting the trends associated with being a ‘true Indian’, R.K. Narayan, who is celebrated as a pure and simple writer, affirms the values of life and reposes faith in moral order in his novels. At the time when he started writing, Indian society underwent a sea change. Social reformers and intellectuals were busy in redefining the image of an Indian woman. Narayan also felt the pressure of the prevalent ideology and put forward the idea of what it is to be an ideal Indian woman and created a female character named Bharati in his novel Waiting for the Mahatma (1955). The novel is seen as a ‘liberation fable’ with Bharati as the central character who is viewed as a crocus of an ideal Indian woman. Her view of life is considered viable and authentic. Critics opine that Bharati, who is bold, self-dependent, and strong is an example of Narayan’s true vision of women’s empowerment. Although when her character is studied closely, it becomes apparent that Bharati internalizes myths and accepts roles that afford her no real choices and no real values. She perfectly resembles traditional women who possess neither agency nor any will of their own and spend their energy in the service of patriarchy. Even though Bharati radiates through the novel and finds a space, her attributes as a volitional force reserved for Sriram suggest that she is the subject of the novel who lacks artistic expression and self-assertion. Narayan, despite his awareness about the predicament of an Indian woman and his sincere effort to be judicious towards woman, fails to transcend the forces of history that allows him to look at women with stereotypical vision.